2018
DOI: 10.1371/journal.pone.0195147
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking is a risk factor for the onset of fatty liver disease in nondrinkers: A longitudinal cohort study

Abstract: BackgroundThe effect of cigarette smoking on the onset of nonalcoholic fatty liver disease (NAFLD) is unclear, especially that associated with drinking small amounts of alcohol. We conducted a longitudinal study to investigate the relationship between cigarette smoking and NAFLD onset, which was stratified according to the amount of alcohol consumed.MethodsWe enrolled 7,905 Japanese subjects who had received annual health checkups more than twice between April 2003 and August 2013, 4,045 of whom met at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
3
30
0
2
Order By: Relevance
“…There have been several longitudinal cohort studies on lifestyle habits involved in the development or remission of NAFLD. However, most of these studies assessed lifestyle habits at baseline but not changes in these habits during the study period 14,[16][17][18]26 . We conducted a longitudinal cohort study to investigate the association of the development or remission of NAFLD with favorable changes in the lifestyle habits during follow-up period: weight loss, starting to exercise, quitting smoking, and stopping eating dinner within 2 hours of going to bed.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several longitudinal cohort studies on lifestyle habits involved in the development or remission of NAFLD. However, most of these studies assessed lifestyle habits at baseline but not changes in these habits during the study period 14,[16][17][18]26 . We conducted a longitudinal cohort study to investigate the association of the development or remission of NAFLD with favorable changes in the lifestyle habits during follow-up period: weight loss, starting to exercise, quitting smoking, and stopping eating dinner within 2 hours of going to bed.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that these flaws are balanced by the benefits of this large study, and the ability to generalize these results to the population. As the mechanism of the association between NAFLD and smoking remains controversial, future prospective studies should investigate the underlying mechanisms of this association. In addition, future studies are needed to elucidate the effects of active and passive smoking on NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that exposure to environmental toxicants, including secondhand smoke (SHS), contributes to the development of NAFLD by promoting mitochondrial dysfunction and oxidative stress within the hepatocytes [9][10][11][12]. Several studies have shown that cigarette smoking is an independent risk factor for the onset of NAFLD [13][14][15][16], and significantly associated with increased intrahepatic fat [17] and advanced liver fibrosis [18,19]. Survey based reports have also shown an association between exposure to SHS and development of NAFLD in children [20,21] and in never-smoking women [22].…”
Section: Introductionmentioning
confidence: 99%